STUDENTS' MATHEMATICAL PROBLEM-SOLVING SKILLS ON CONGRUENCE MATERIAL IN RELATION TO INTRAPERSONAL INTELLIGENCE - Afifah, Nur; Mirza, Ade; Siregar, Nurfadilah; Bistari; Pasaribu, Revi Lestari; Wicaksono, Luhur (KALAMATIKA Jurnal Pendidikan Matematika, 2025)
Intrapersonal intelligence can help students solve mathematical problems, and each student has different abilities depending on their level of intelligence. This study aimed to determine and explain students' mathematical problem-solving skills on congruence material in relation to intrapersonal intelligence. A qualitative approach with a case study design was used. The instruments included an intrapersonal intelligence questionnaire, a mathematical problem-solving skills test, and an interview guide. The results show that students' intrapersonal intelligence falls into three categories: high (21.43%), medium (60.71%), and low (17.86%). Students with high intrapersonal intelligence were able to fulfill all four indicators of mathematical problem-solving skills: understanding the problem, planning the solution, implementing the solution plan, and reviewing the solution. Students with medium intrapersonal intelligence were able to fulfill three indicators: understanding the problem, planning the solution, and implementing the solution plan. Students with low intrapersonal intelligence were able to fulfill two indicators: understanding the problem and planning the solution.